Association between albumin-to-alkaline phosphatase ratio and a 3-month unfavorable outcome in patients with acute ischemic stroke - Zhang, Renwei; Liu, Zhenxing; Cai, Qi; Xie, Yu; Liu, Yumin; Peng, Li (Frontiers in Nutrition, 2025)
BackgroundThe albumin-to-alkaline phosphatase ratio (AAPR) is a predictor of several disease outcomes. However, there is no study about AAPR and acute ischemic stroke outcomes. This study aims to investigate the relationship between AAPR and a 3-month unfavorable outcome in patients with acute ischemic stroke.MethodsThis prospective cohort study included 2084 patients with acute ischemic stroke in South Korea. After applying strict exclusion criteria, 1,886 patients were included in our analysis and divided into three groups based on AAPR tertiles. An unfavorable outcome was defined as a 3-month modified Rankin scale (mRS) score > 2. Logistic regression analysis and smooth curve fitting analysis were applied to investigate the relationship between AAPR and unfavorable outcomes. Subgroup analysis was also performed to assess whether influencing factors changed the association between AAPR and unfavorable outcomes.ResultsAfter adjusting for potential confounders, multivariate analysis showed that AAPR was significantly associated with a 3-month unfavorable outcome (OR 0.18, 95% CI 0.09–0.35, p < 0.001). The smooth curve fitting analysis showed a nonlinear relationship between AAPR and a 3-month unfavorable outcome. The infection point was 0.588 according to the recursive method, and the threshold analysis showed when AAPR was ≤0.588, with the per unit increase of AAPR, the 3-month unfavorable outcome risk decreased by 96% (OR 0.04, 95% CI 0.01–0.2, p < 0.001). However, when AAPR was >0.588, there was no negative correlation between AAPR and a 3-month unfavorable outcome (OR 0.33, 95% CI 0.08–1.3, p = 0.112).ConclusionThis study is the first to suggest a non-linear relationship between AAPR and a 3-month unfavorable outcome of acute ischemic stroke. AAPR was negatively correlated with a 3-month unfavorable outcome when AAPR was <0.588.